Closely related benzylene-linked diamidophosphine scaffolds and their zirconium and hafnium complexes: how small changes of the ligand result in different complex stabilities and reactivities - Batke, Sonja; Sietzen, Malte; Merz, Lukas; Wadepohl, Hubert; Ballmann, Joachim (Organometallics, 2016)
The closely related benzylene-linked diaminophosphines PhP(CH2C6H4-o-NHPh)2 ([PhA]H2) and PhP(C6H4-o-CH2NHXyl)2 ([B]H2) were prepared as robust alternatives to the previously reported N,N′-bis(trimethylsilyl)-substituted derivative PhP(CH2C6H4-o-NHSiMe3)2 ([SiA]H2). Upon reaction of [PhA]H2 and [B]H2 with M(NMe2)4 (M = Zr, Hf), the respective dimethylamido complexes [PhA]M(NMe2)2 and [B]M(NMe2)2 ([PhA]-1-M and [B]-1-M, M = Zr, Hf) were isolated in high yields and converted to the corresponding diiodo derivatives [PhA]MI2 and [B]MI2 ([PhA]-2-M and [B]-2-M, M = Zr, Hf). In contrast to [SiA]ZrI2, these thermally robust diiodo complexes were found to react cleanly with Bn2MgL2 (L = THF or Et2O), resulting in the corresponding dibenzyl species [PhA]MBn2 and [B]MBn2 ([PhA]-4-M and [B]-4-M, M = Zr, Hf). Upon addition of [B]H2 to [B]ZrBn2, the related homoleptic species [B]2Zr ([B]-5-Zr) was generated. Similar 2:1 complexes have not been observed for the hafnium homologue bearing the latter ligand or for [SiA]- or [PhA]-coordinated complexes. The former dibenzyl complexes were reacted with 2,6-xylylisonitrile, and clean conversions to the bis-η2-iminoacyl complexes [B]-6-Hf and [PhA]-6-M were observed for [B]-4-Hf and [PhA]-4-M (M = Zr, Hf). For [SiA]HfBn2 ([SiA]-4-Hf) only one equivalent of the former isonitrile was inserted into one of the hafnium carbon bonds, which is in line with the steric differences between [SiA] and [PhA].